The personal and scientific life of Imam Ibn Abi Khaythamah - Yousra Hussein Salloum,; Khaled Mustafa Muhammad, (Islamic Sciences Journal, 2024)
ABSTRACT Since the Prophet’s Sunnah is the second source of Islamic legislation after the Qur’an, and it is the clarification of the Qur’an, the detail of its entirety, the restriction of its absolutes, and the specification of its generality, it received the attention of our righteous predecessors in its preservation, endurance, performance, and journey. They preserved the hadith of the Messenger of Allah , may Allah bless him and grant him peace, and protected him. From the false intruder, and they made great efforts in clarifying the circumstances of the narrators, authenticating and weakening, wounding and modifying, with what is known as the science of wounding and modification, and they delved into the knowledge of the reasons for the hadith, so Allah rewarded them on our behalf with the best reward. Among those who made an effort in this field were Imam Abu Bakr Ahmad ibn Zuhair ibn Abi Khaythamah, and Imam Yahya ibn Ma’in Abu Zakaria al-Baghdadi, where I found their sayings about men that were offensive and correct, through questions directed by Ibn Abi Khaythamah to Ibn Ma’in, or through him listening to him. He modifies, authenticates, or criticizes the narrators. It is known that Abu Zakaria Yahya Ibn Ma’in was an authority in criticizing men. Paying attention to his expressions is a science in itself, and we are truly in front of two imams who are distinguished in various arts of knowledge and who have an unparalleled reputation in defending the menstruation of the Sunnah, through a clarification. The conditions of the narrators. This study deals with Ibn Abi Khaythamah, and explains something from his life, may Allah have mercy on him.